2011
DOI: 10.1042/bj20110351
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the transmembrane and juxtamembrane domains enhance IL27R transforming activity

Abstract: Synopsis Cytokines and their receptors regulate hematopoiesis by controlling cellular growth, survival, and differentiation. Thus, it is not surprising that mutations of cytokine receptors contribute to the formation of hematopoietic disorders including cancer. We recently identified transforming properties of the ligand-binding component of the receptor for interleukin-27 (IL27R). While wildtype IL27R exhibits transforming properties in hematopoietic cells, in this study we set out to determine if the transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Consistent with this observation, IL-27 promoted cell survival of the leukemic cell lines. Our data are in agreement with previous studies (Pradhan and others 2007 , 2010 ; Seita and others 2008 ; Rousseau and others 2010 ; Lambert and others 2011 ). Through functional screening approaches, Pradhan and others ( 2007 , 2010 ) identified IL-27R as a transforming gene from the leukemic cells of a patient with AML and showed that IL-27R is highly expressed on the cell surface of bone marrow cells of AML patients compared with the normal bone marrow cells.…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with this observation, IL-27 promoted cell survival of the leukemic cell lines. Our data are in agreement with previous studies (Pradhan and others 2007 , 2010 ; Seita and others 2008 ; Rousseau and others 2010 ; Lambert and others 2011 ). Through functional screening approaches, Pradhan and others ( 2007 , 2010 ) identified IL-27R as a transforming gene from the leukemic cells of a patient with AML and showed that IL-27R is highly expressed on the cell surface of bone marrow cells of AML patients compared with the normal bone marrow cells.…”
Section: Discussionsupporting
confidence: 94%
“…Three cytokine receptors are expressed on EWS: IL17RE, IL27RA, and IL1RAP. A recent mutational study demonstrated that IL27RA has transforming potential, although its expression on non-lymphoid malignancies has not previously been described (Lambert et al, 2011). IL1RAP, Interleukin-1 receptor accessory protein, can exist as a membrane or soluble form and is essential for IL-1 receptor activity.…”
Section: Resultsmentioning
confidence: 99%
“…By unravelling the activation mechanism for these receptors, valuable insights for novel approaches in developing clinically relevant drugs will be gained. The critical nature of the ECD linker and TMDs is highlighted by a number of clinical and experimentally introduced activating mutations for a number of class I cytokine receptors including TPOR (S505N) [ 100 ], IL-27R (F523C) [ 115 ], βc (V449E) [ 113 ], and a number of mutations for EPOR [ 116 ] and GHR [ 44 , 51 ]. These studies expose this vital region as a potential Achilles’ heel for this class of cytokine receptors.…”
Section: Discussionmentioning
confidence: 99%